Development of Items Designed to Evaluate Activity Performance and Participation in Children and Adolescents with Spinal Cord Injury. (7th October 2009) - Calhoun, Christina L.; Haley, Stephen M.; Riley, Anne; Vogel, Lawrence C.; McDonald, Craig M.; Mulcahey, M. J.
Abstract : Background/Objective . Outcomes-based data, whether used clinically or for research, are difficult to collect in the pediatric spinal cord injury (SCI) population due to a lack of appropriate assessment measures. The purpose of this paper is twofold: to describe the process by which two item pools were developed to evaluate activity performance and participation among children with SCI and to introduce the resultant items specific to pediatric SCI. Methods . The process of item development, including construct development, review of related assessment tools, chart review, item writing and refinement using focus groups, cognitive interviews, and further refinement, was used to create the items pools for activity and participation for children and adolescents with SCI. Results . A total of 347 items were written for the activity performance construct and 61 items were written for the participation construct. Several domains were established within each construct and items were written for both child and parent respondents. Conclusion . The process of detailed item development is the first step in the process of developing an outcomes instrument for children and adolescents with SCI to assess activity performance and participation. The items are representative of pediatric SCI because they address areas specific to children and adolescents with SCI such as wheeled mobility, upper extremity function with adaptive equipment, role performance, and socialization. After testing these items in calibration studies, we will determine if these items can be developed into effective computer-adaptive testing applications.